Optimasi Pengalaman Pengguna: Evaluasi ISO/IEC 25010 pada Penjualan Online - Surachman, Arie (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2024)
This study explores improving user experience on online sales platforms using ISO/IEC 25010 standards. It focuses on enhancing customer satisfaction with Tokopedia, Shopee, and Lazada. The research uses case studies and Likert scale surveys to evaluate critical aspects like reliability, security, and system efficiency. The goal is to provide insights into factors affecting user experience in online sales. The ISO/IEC 25010 evaluation results aim to guide system improvements, ensuring user needs are met. This research significantly contributes to understanding the online sales market dynamics, helping stakeholders take strategic steps to create a more effective and satisfying platform for users.